Femtosecond Laser-Assisted Penetrating Keratoplasty for Treating Infective Keratitis. Issue 3 (March 2020) - Hosny, Mohamed; Marrie, Ayah; Anis, Mohamed; El Shewy, Ahmed
Abstract : Purpose: To report the results of penetrating keratoplasty (PKP) assisted by femtosecond laser in the treatment of persistent infective keratitis. Methods: Seven eyes of 7 patients with diagnosed infective keratitis were recruited. They showed no improvement on maximal medical therapy for a week. The causative organisms were Pseudomonas aeruginosa in 3 cases and Fusarium in 4 cases. All cases underwent femtosecond laser-assisted PKP with a mushroom-shaped cut. Postoperative antimicrobial medications were continued for 8–12 weeks. Sutures were removed after 6 months. Therapeutic success was defined as eradication of primary infection. Functional success was considered when visual function improves to 20/200 or better. Results: All 7 eyes underwent femtosecond laser-assisted PKP. There were no intraoperative complications, and all patients had uneventful recipient cornea separation. Anatomic, therapeutic, and functional success was achieved in all patients. During the 6-month follow-up period, no recurrence of infection was reported. The average preoperative corrected distance visual acuity (CDVA) was 2.07 log of the minimal angle of resolution (LogMAR) ± 0.21, whereas at 6 months postoperatively, the average CDVA was 0.17 LogMAR ± 0.13, with a P value of 0.00025. Conclusions: Femtosecond laser-assisted PKP was found to be an effective method for treating infective keratitis (particularly that caused by Pseudomonas aeruginosa and Fusarium ) that did not respond to medical treatment. Early surgical intervention before the disease becomes advanced is recommended.